EFEKTIVITAS DAN TANTANGAN E-LEARNING TAHSIN DAN TAFSIR: INTEGRASI AL DAN PERILAKU GEN Z - Loka, Dara Puspita; Bashori, Bashori (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2025)
The digital transformation of Islamic education has opened new avenues for Qur"™anic instruction, particularly in the domains of tahsin (Qur"™anic recitation) and tafsir (interpretation) through e-learning platforms. Among Generation Z learners, who are digital natives with a strong preference for interactive and flexible learning environments online learning has gained popularity. However, the phonetic precision required in tahsin and the conceptual depth of tafsir present unique challenges to effective delivery via digital platforms. This study aims to explore the effectiveness and challenges of Qur"™anic e-learning by analyzing the integration of Artificial Intelligence (AI) technologies and the learning characteristics of Gen Z. Using a qualitative descriptive approach, data were obtained from academic literature, platform analysis (such as Tarteel and Ngaji.ai), and documentation from existing studies. Findings indicate that AI enhances learning through adaptive features such as voice recognition, microlearning, and gamification. Nevertheless, limitations persist in terms of emotional engagement, spiritual mentoring, and the depth of interpretative understanding. This research provides a novel synthesis of digital pedagogy, AI technology, and Gen Z learning behavior in the context of Islamic education. It recommends a hybrid learning model that balances technological innovation with human mentorship to ensure that Qur"™anic education remains comprehensive, spiritually enriching, and pedagogically effective for the digital generation.